The fifth International Conference on Inertial Fusion Sciences and Applications (IFSA2007) - Azechi, Hiroshi; Hammel, Bruce; Gauthier, Jean-Claude (Journal of physics. Conference series, 2008)
The Fifth International Conference on Inertial Fusion Sciences and Applications (IFSA 2007) was held on 9–14 September 2007 at Kobe International Conference Center in Kobe, Japan. The host organizations for this conference were Osaka University and the Institute of Laser Engineering (ILE) at Osaka University; and co-organized by the Institute Lasers and Plasmas (ILP) in France, the Commissariatá l'Energie Atomique (CEA), Lawrence Livermore National Laboratory (LLNL), National Institute for Fusion Science (NIFS) in Japan, and Kansai Photon Science Institute (KPSI), Japan Atomic Energy Agency (JAEA). The conference objective was to review the state of the art of research in inertial fusion sciences and applications since the last conference held in Biarritz, France, in 2005. 470 abstracts were accepted, and 448 persons from 18 countries attended the conference. These Proceedings contain 287 of the papers presented at IFSA 2007. This collection of papers represents the manuscripts submitted to and passing the peer review process. The program was organized with some specific features: The reviews of influential programs appeared both at the very beginning and at the very end of the Conference to attract attendance throughout the Conference. Each poster session had the same time period as a single oral session, thereby avoiding overlap with oral talks. The everyday program was structured to be as similar as possible so the attendees could easily recognize the program. With a goal of achieving inertial fusion ignition and burn propagation in the laboratory, researchers presented the exciting advances in both traditional hot spot ignition and fast ignition approach, including status report of USA's National Ignition Facility (NIF), French Laser Magajoule (LMJ), Japanese Fast Ignition Realization Experiment (FIREX), and European High Power laser Energy Research (HiPER). A particular emphasis of the meeting was that the `physics of inertial fusion' category was dominated by fast-ignition and related ultra-intense laser interaction. Progress in direct drive over the past few years resulted in the achievement of high-density cryogenic implosions at OMEGA. Continuous progresses in hohlraum physics gave confidence in the achievement of ignition at NIF and LMJ. Advances in Z-pinch included double-hohlraum irradiation symmetry and the PW laser beam for the Z-facility. Progress of laser material development for IFE driver was a very interesting topic of inertial fusion energy drivers, including KrF and DPSSL lasers and particle beams. Of special interest, a future session was focused on strategy of inertial fusion energy development. Laboratory tours were held in the middle of the Conference. The Laser for Fusion EXperiments (LFEX), a new high-energy petawatt laser at ILE, was one of the key attractions of IFSA 2007. 83 participants toured LFEX and GEKKO XII lasers, and 35 joined a tour of KPSA-JAEA. In parallel to the tour, the `Symposium on Academics-Industries Cooperation for Applications of High-Power Lasers' was held with more than 90 participants mostly from the industrial community. These Proceedings start with special chapters on the keynote and focus speeches and the Teller lectures. The keynotes and focus give an overview of progress in inertial fusion in Asia, North America, and Europe. The Teller lectures show the contributions of this year's two winners: Brian Thomas of AWE, UK and Kunioki Mima of ILE. The remainder of the Proceedings is divided into three parts. Part A covers the physics of inertial fusion; Part B covers laser, particle beams, and fusion technology including IFE reactors and target fabrication; and Part C covers science and technology applications such as laboratory astrophysics, laser particle acceleration, x-ray and EUV sources, and new applications of intense lasers. These parts are further divided into chapters covering specific areas of science or technology. Within each chapter the talks relevant to that subject are gathered. The IFSA International Organizing Committee and Scientific Advisory Board appreciate the efforts of inertial fusion researchers worldwide in making IFSA 2007 an extremely successful conference. The proceedings were published with the support of Dr Y Sakawa, Dr H Homma, Ms S Karasuyama, Ms M Odagiri, and Ms I Kobatake. Kunioki Mima Co-chair Hiroshi Azechi Technical Program Committee Co-chair John Lindl Co-chair Bruce Hammel Technical Program Committee Co-chair Christine Labaune Co-chair Jean-Claude Gauthier Technical Program Committee Co-chair